2009
DOI: 10.1109/ted.2009.2031043
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hole Transport in Short-Channel Strained-SiGe p-MOSFETs

Abstract: Hole mobility and velocity are extracted from scaled strained-Si 0.45 Ge 0.55 channel p-MOSFETs on insulator. Devices have been fabricated with sub-100-nm gate lengths, demonstrating hole mobility and velocity enhancements in strained-Si 0.45 Ge 0.55 channel devices relative to Si. The effective hole mobility is extracted utilizing the dR/dL method. A hole mobility enhancement is observed relative to Si hole universal mobility for shortchannel devices with gate lengths ranging from 65 to 150 nm. Hole velocitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…2 One of the challenges for the SiGe devices poses the formation of germanosilicide with pristine electrical and structural properties, namely, a low electrical resistivity, an abrupt and uniform interface to SiGe, as well as a low contact resistance.…”
mentioning
confidence: 99%
“…2 One of the challenges for the SiGe devices poses the formation of germanosilicide with pristine electrical and structural properties, namely, a low electrical resistivity, an abrupt and uniform interface to SiGe, as well as a low contact resistance.…”
mentioning
confidence: 99%
“…The piezoresistance coefficient of a longitudinal configuration of the [1 1 0] p-type strained SiGe channel is positive (125 GPa), whereas that of the transverse configuration is negative (À52 GPa) [5]. Moreover, the large and small W/L ratios indicate that the channels are transverse configuration dominant ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The strained layer enhances the hole mobility and is compatible with the CMOS process. Many studies have reported that a long p-channel is enhanced more than a short channel is [1][2][3][4][5]. Increasing the channel length augments the hole velocity and mobility in a SiGe channel [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…≡D lattice [10] ) unless CC License in place (see abstract In Equation 10, the degree of relaxation R appears in two places, (1 − R) 2 in the large parenthesis for the driving force change and (1 − R) in the exponent term for the interdiffusivity change. When the R value equals 1, we can see that the apparent interdiffusivity equalsD relax , where there is no strain impact.…”
Section: Gementioning
confidence: 99%